Attitudes of Malaysian university students towards six English accents - Pilus, Zahariah (2014)
This study examines the attitudes of 115 students at a Malaysian university towards British, American, Australian, New Zealand, Singaporean and Malaysian English accents. The students responded to a questionnaire which included questions on English accents adapted from Jenkins (2007). The students were required to do the following: (1) list three best English accents (2) rate the British, American, Australian, New Zealand, Singaporean and Malaysian English accents with respect to familiarity, correctness, pleasantness and acceptability in international communication (3) label their own accents and (4) choose a model for the teaching of pronunciation in Malaysia. Analyses of the responses among others showed that the students generally have a strong preference for native English accents. These findings highlight preferences and concerns in pronunciation learning which ought to be given due consideration since speakers’ attitudes towards accents can have considerable pedagogical implications especially in a second or foreign language context.